2023
DOI: 10.1101/2023.06.05.543674
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss of Lamin A leads to the nuclear translocation of AGO2 and compromised RNA interference

Vivian Lobo,
Iwona Nowak,
Carola Fernandez
et al.

Abstract: In mammals, RNA interference (RNAi) is mostly studied as a cytoplasmic event, however, numerous reports convincingly show nuclear localization of the AGO proteins. Nevertheless, the mechanism of nuclear entry remains to be fully elucidated, and the extent of nuclear RNAi further explored. We found that reduced Lamin A levels significantly induced nuclear influx of AGO2 in SHSY5Y neuroblastoma and A375 melanoma cancer cell lines, which normally have no nuclear AGO2. The translocation of AGO2 was accompanied by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 102 publications
0
6
0
Order By: Relevance
“…This adds to the multiple proviral roles of NS1 56 . A limited number of previous reports already identified nuclear presence of AGO2 upon IAV infection 22,57 , however both utilized cell lines (A549 and HEK293T) which are already nuclear-AGO positive at steady state 25 , thus complicating the interpretation of the results. Herein, by using HEK293 cells, which are nuclear AGO negative at steady state, we could better mimic what happens in mouse lungs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This adds to the multiple proviral roles of NS1 56 . A limited number of previous reports already identified nuclear presence of AGO2 upon IAV infection 22,57 , however both utilized cell lines (A549 and HEK293T) which are already nuclear-AGO positive at steady state 25 , thus complicating the interpretation of the results. Herein, by using HEK293 cells, which are nuclear AGO negative at steady state, we could better mimic what happens in mouse lungs.…”
Section: Discussionmentioning
confidence: 99%
“…AGO2 may localize both in the cytoplasm and the nucleus of human cells 25 . For instance, we previously demonstrated the absence of nuclear AGO2 in HEK293 cells 21,25 However, we observed a high degree of nuclear AGO2 in HEK293T cells, which are HEK293 cells transformed with SV40 large T (LT) antigen, the master regulator of polyomaviruses 26 To address this, we took advantage of PR8 strain of IAV as a model system. HEK293 cells were infected with PR8-IAV at several multiplicity of infection (MOI) 10 for 16 IAV consists of eight gene segments that encode up to 17 viral proteins 28 .…”
Section: Viral Infection Induces Nuclear Accumulation Of Ago2mentioning
confidence: 99%
See 1 more Smart Citation
“…Improved purification protocols that exclude endoplasmic reticulum from nuclear lysate, however, demonstrated that AGO protein and miRNAs were present in cell nuclei ( 10 , 11 , 13 , 16 , 34 , 42 , 44 , 47 , 63 , 78 , 93 ). miRNAs were demonstrated to load in cell cytoplasm prior to transport into the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…For example, transcription factors such as p53 or NF-Kβ are mainly located in the cytoplasm, but upon receiving an activation signal they translocate into the nucleus and interact with specific DNA loci to mediate the transcription of target genes (Liu et al, 2018). Another protein, Argonaute 2 (AGO2), the main component of RNA interference pathway is usually found within the cytoplasm, yet, in some conditions, such as cell confluence or certain cancers, can relocate to the nucleus (Huang et al, 2024;Johnson et al, 2023;Lobo et al, 2024;Sarshad et al, 2018). Therefore, an appropriate protocol to identify and separate the subcellular protein localization is critical to understand the physiological function of shuttling and localized proteins.…”
mentioning
confidence: 99%